Multi-biomarker analysis in patients after transcatheter aortic valve implantation (TAVI). (17th November 2018) - Mirna, Moritz; Wernly, Bernhard; Paar, Vera; Jung, Christian; Jirak, Peter; Figulla, Hans-Reiner; Kretzschmar, Daniel; Franz, Marcus; Hoppe, Uta C.; Lichtenauer, Michael; Lauten, Alexander
Abstract: Background: In this study we sought to examine whether transcatheter aortic valve implantation (TAVI) is followed by a change in the plasma levels of novel cardiovascular biomarkers. Methods: We collected blood samples of 79 patients with severe aortic valve stenosis undergoing TAVI before and at 7 days, 1 month, 3 months and 6 months post TAVI and analyzed the plasma concentrations of GDF-15, H-FABP, fetuin-A, galectin 3, sST2 and suPAR by means of ELISA. Results: There was a significant increase in the concentration of fetuin-A (median: 52.44 mg/ml to 113.2 mg/ml, p < 0.001) and a significant decrease of H–FABP after TAVI (median: 4.835 ng/ml to 2.534 ng/ml, p < 0.001). The concentrations of suPAR and sST2 showed an initial increase (suPAR median: 2755 pg/ml 3489 pg/ml, p < 0.001; sST2 median: 5832 pg/ml to 7137 pq/ml, p < 0.001) and subsequently decreased significantly. Conclusion: We hypothesize that the decrease of H-FABP and the increase of fetuin-A could be due to a hemodynamic improvement after valve replacement. The initial increase of suPAR could indicate an inflammatory stimulus and the significant increase in sST2 could be due to the mechanical strain caused by implantation of the valve.